PENGARUH KUALITAS PERANGKAT LUNAK TERHADAP KEPUTUSAN PEMBELIAN MOBILEPHONE BERBASIS ANDROID PADA MASYARAKAT PENDIDIKAN DI KOTA BATAM - amrizal amrizal (Computer Based Information System Journal, 2015)
The development of technology information has brought changing to decision to the way of making decision in purchasing the technologi of mobilephone; particulary, the quality of software as the part of inprovement mobile phone. On the other hand, people tend to leave their mobile phone as soon as the growth of technologi. This fact leads the producer of mobile phone to keep improving the quality as sociaty need; one of them is the quality of software of the mobile phone. Thus, the producers of this tecnology need to deal with the business development and society need in competitive ways.